Chronic constipation – is it possible to treat effectively and safetly? - Bednarczuk, Arkadiusz; Rydzewska, Grażyna (Przewodnik Lekarza/Guide for GPs, 2005)
Chronic constipation is one of the most common complaints among the population of high developed countries, recently also in Poland. It is crucial to differentiate the chronic constipation from constipation due to external factors e.g. drugs. Due to chronic nature of the disease the treatment is usually difficult and sometimes not effective. Despite broad range of laxatives available on the market it is still difficult to reach both the therapeutic effect and complete safety of the product used. Most troublesome cases of constipation, resistant to pharmacological treatment and being of the direct risk to their general condition, are the indication for surgical treatment.